Blood Relations. - Jeffs, Sandy, 1953- (Spinifex Press, 2000)
These poems are an evocative documentation of the harrowing experiences of a child living in a hostile and unhappy home. Pain and bitterness accompany the conflicting emotions of growing up in a family torn apart by domestic violence and alcoholism.